Condensation of bioderived guaiacol with acetaldehyde for the synthesis of bisguaiacol-E: a biobased alternative to bisphenol-A - Dhotre, Kapil; Tarade, Komal P.; Kamble, Sanjay P. (Industrial & Engineering Chemistry Research, 2026)
Bisguaiacol-E (BGE) has emerged as a biobased and sustainable alternative to bisphenol-A (BPA) for the production of materials intended for direct contact with humans and animals, including baby feeding bottles and food packaging. In the present study, BGE was synthesized from bioderived guaiacol and acetaldehyde via acid-catalyzed condensation using a highly efficient and reusable ion-exchange resin, Purolite C124SH. Under optimized conditions, the process achieved 96% guaiacol conversion with 100% selectivity toward BGE. The crude product was purified to obtain BGE in 95% isolated yield and 100% purity. The reusability of Purolite C124SH was evaluated over multiple reaction cycles. After five consecutive reuse cycles, guaiacol conversion and BGE selectivity declined by approximately 25-26% and 20-22%, respectively. However, after regeneration by methanol treatment, the catalyst recovered its activity and maintained a consistent performance over the subsequent three cycles. These results demonstrate the catalyst's regenerability, robustness, and resistance to deactivation, highlighting its potential for cost-effective industrial application. The kinetic study indicates that the condensation of acetaldehyde with guaiacol to form BGE over the Purolite C124SH resin catalyst can be described by a pseudohomogeneous kinetic model. The reaction follows apparent pseudo-first-order behavior, with an activation energy of 43.5 kJ mol-1, suggesting a minimal contribution from external mass-transfer limitations under the investigated conditions. Moreover, at the optimized reaction conditions, the estimated space-time yield (STY) was 0.42 kg L-1 h-1, corresponding to an apparent reaction rate constant of 0.5 h-1. Furthermore, the physicochemical properties of the synthesized BGE were compared with those of reported BGF (Bisguaiacol-F) and BPA, showing strong alignment and confirming its applicability as a safer substitute. The environmental performance of the process was assessed using green chemistry metrics. The calculated E-factor (0.2) and Process Mass Intensity (PMI - 1.27) indicate low waste generation, high material efficiency, and improved sustainability. Overall, the developed methodology offers a clean, efficient, and scalable route for producing BGE as a viable biobased replacement for BPA.